Life-Long Hyperbilirubinemia Exposure and Bilirubin Priming Prevent In Vitro Metabolic Damage - Bianco, Annalisa; Pinci, Serena; Tiribelli, Claudio; Bellarosa, Cristina (Frontiers in Pharmacology, 2021)
Background: Unconjugated bilirubin (UCB) is more than the final product of heme catabolism. Mildly elevated systemic bilirubin concentrations, such as in Gilbert syndrome (GS), protect against various oxidative stress-mediated and metabolic diseases, including cardiovascular disease, type 2 diabetes mellitus, metabolic syndrome, cancer, and age-related disease. The Gunn rat is an animal model of hereditary hyperbilirubinemia widely used in assessing the effect of high serum bilirubin concentration in various organs. The present work aims to understand if life-long hyperbilirubinemia and bilirubin-priming might contribute to protection against atherosclerosis and diabetic nephropathy (DN) at the cellular level. Methods: Primary aortic endothelial cells and podocytes obtained from hyperbilirubinemic homozygous jj and normobilirubinemic heterozygous Nj Gunn rats were exposed to Palmitic Acid (PA) and Angiotensin II (Ang II), respectively, and the effects on cell viability and the activation of damage-related metabolic pathways evaluated. Results were validated on immortalized H5V and HK2 cells exposed to damage after UCB pretreatment. Results: In both primary cell models, cells obtained from jj Gunn rats showed as significantly higher than Nj Gunn rats at any dose of the toxic agent. Reduction in CHOP expression and IL-6 release was observed in jj primary aortic endothelial cells exposed to PA compared to Nj cells. The same occurred on H5V pretreated with UCB. Upon Ang II treatment, primary podocytes from jj Gunn rats showed lower DNA fragmentation, cleaved caspase-3, and cleaved PARP induction than primary podocytes from Nj Gunn rats. In HK2 cells, the induction by Ang II of HIF-1α and LOXl2 was significantly reduced by UCB pretreatment. Conclusions: Our data suggest that in models of atherosclerosis and DN life –long hyperbilirubinemia exposure or bilirubin-priming significantly contribute to decrease the injury by enhancing the cellular defensive response.